1970
DOI: 10.1021/jf60169a037
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mobility and adsorption of agrochemicals on soils

Abstract: Movement of certain agricultural chemicals in soil was studied in the laboratory by measurement of the Ri values of monuron, diuron, bromacil, terbacil, and chloroneb on thin layers (400 p) of soil deposited on glass plates and developed in water, and by determination of the Freundlich isotherm constants (K) of these chemicals in soil-water systems. The relationship of the Freundlich constants (K) to the Ri values is discussed. An empirical equation relating these constants for the above agrichemicals on Keypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 9 publications
1
28
0
1
Order By: Relevance
“…3 and 4). The slope of the isotherm steadily decreases with rise in solute concentration because of vacant sites become less accessible with the progressive covering of the surface (Rhodes et al 1970). Nonlinear isotherm indicates that a number of available sites for the sorption become a limiting factor, which may be due to the fact that flubendiamide molecules occupy most of the sorption sites at the higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4). The slope of the isotherm steadily decreases with rise in solute concentration because of vacant sites become less accessible with the progressive covering of the surface (Rhodes et al 1970). Nonlinear isotherm indicates that a number of available sites for the sorption become a limiting factor, which may be due to the fact that flubendiamide molecules occupy most of the sorption sites at the higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Malik & Drennan (1989) observaram aumentos na sorção do fluridone ao utilizarem a relação 1:1, comparada com a relação 1:5. Vários autores (Oliveira, 1995;Rhodes et al, 1970;Roowell, 1994;Schroeder, 1994) também constataram que aumentos nos teores de CO resultam em aumentos na afinidade dos pesticidas pelo solo. Assim como observado por Werkheiser & Anderson (1996), verifica-se que, à exceção do LE, para solos com pH semelhante, os maiores coeficientes de sorção para o flazasulfuron foram obtidos nos solos com maiores teores de CO.…”
Section: Sorção/dessorção Do Flazasulfuronunclassified
“…It is suggested that the relltwe adsorption/desorption potentiat of a herbicide may provide i-mechanism by which soil applied herbicides can be biologically inactivated more readily in soils of high organic matter content. (Harris and Sheets 1965), phytotoxicity and mobility of monuron (Harris 1966), and mobility of monuron (May 1975) and diuron (Rhodes et al 1970;Helling 1971) were correlated with the extent of adsorption on the soils studied. The adsorption of a number of urea herbicides has been studied in a variety of soils.…”
mentioning
confidence: 90%